New lists: Fundamentals and survival rates - Fama, Eugene F; French, Kenneth R (Journal of Financial Economics, 2004)
The class of firms that obtain public equity financing expands dramatically in the 1980s and 1990s. The number of new firms listed on major U.S. stock markets jumps from 156 per year for 1973–1979 to 549 per year for 1980–2001. The characteristics of new lists also change. The cross section of profitability becomes progressively more left skewed, and growth becomes more right skewed. The result is a sharp decline in survival rates. We suggest that the changes in the characteristics of new lists are due to a decline in the cost of equity that allows weaker firms and firms with more distant expected payoffs to issue public equity.